Polyether ionophore resistance in a one health perspective - Frederiksen, Rikki Franklin; Slettemeås, Jannice Schau; Granstad, Silje; Lagesen, Karin; Pikkemaat, Mariel G.; Urdahl, Anne Margrete; Simm, Roger (Frontiers in Microbiology, 2024)
Antimicrobial resistance is a major threat to human health and must be approached from a One Health perspective. Use of antimicrobials in animal husbandry can lead to dissemination and persistence of resistance in human pathogens. Polyether ionophores (PIs) have antimicrobial activities and are among the most extensively used feed additives for major production animals. Recent discoveries of genetically encoded PI resistance mechanisms and co-localization of resistance mechanisms against PIs and antimicrobials used in human medicine on transferrable plasmids, have raised concerns that use of PIs as feed additives bear potential risks for human health. This review summarizes the current knowledge on PI resistance and discusses the potential consequences of PI-usage as feed additives in a One Health perspective.